The Role of HR Practices on Turnover Intentions Directly and Through Organizational Citizenship Behavior in the Banking Sector of Malaysia - Shah, Syed Haider Ali; Sajjad, Shakeel; Ahmed, Najla Abdallah Mohammed; Arshad, Bilal; Kazmi, Munaza; Nawaz, Rab (International Review of Management and Marketing, 2020)
In the recent years, the banking industry of Malaysia has grown rapidly and the roles of employees are undeniable. In todays, dynamic environment banking industry is striving hard to retain the employees in the organization. Employee provides the basis for organization to be successful. The aim of this paper was to investigate the role of HR practices on turnover intentions directly and indirectly through organizational citizenship behavior in banking sector of Malaysia. Data collected through 510 questionnaires from top five banks (by Capital) branches in Kuala Lumpur, Malaysia. In order to investigate the hypotheses, this study applied Structural equation modelling (AMOS). Findings of this study portray that HR practices had negative effect on turnover intentions while the interesting finding is that indirect effect of HR practices through organizational citizenship were also significant. The results are beneficial for top management of banking sector of Malaysia in order to keep motivating employees and to retain them through proper implementation of OCB. To build and align the HR practices and OCB which results in reducing turnover intentions of employees. Keywords: HR Practices, Organizational Citizenship Behavior, Turnover Intentions, SEM. JEL Classifications: H11; S12 DOI: https://doi.org/10.32479/irmm.10760